Ionic content in a firn core from the antarctic plateau Conteúdo iônico em um testemunho de firn do platô antártico - Gerhard, Nicoli P.; Simões, Jefferson C.; Thoen, Isaías U.; Tavares, Flávia A.; Casassa, Gino; Bernardo, Ronaldo T. (My University, 2020)
This work investigates the ionic content of the upper 28.73 m of the BR-IC-2 core (88°01'21.3"S; 82°04'21.7"W) collected during the Chilean-Brazilian Antarctic traverser in the austral summer of 2004/05. The concentrations of the major ions Na+, K+, Mg2+, Ca2+, Cl-, NO3-and SO4 2-and organic acid H3 CSO3-(methanesulfonate-MS-) were determined by Ion chromatography. Dating, based on the correlation between Na+ and nssSO4 2-(non sea salt sulfate) concentrations, the δD isotopic ratio and the identification of volcanic eruption layers (Pinatubo / Cerro Hudson in 1993, Agung in 1965 and possibly Bristol Island in 1936) found an age of 85 years (1918–2003) for the core, with precision of ± 3 years. From this dating, it was possible to establish the mean annual precipitation at this site: 0.15 m eq H2 O. A low contribution of sea salts aerosols and a large crustal and biogenic contribution were found, indicated by the concentrations of nssCa2+ and nssSO4 2-, respectively. The high value of the Cl- / Na+ ratio (4.96) indicates that factors other than the contribution of sea salt contribute to the concentrations of these ions, such as the input or formation of HCl and the lower depletion of Cl-. The K+ and Mg2+ concentrations, although poorly correlated with other ions, are of marine origin. MS- shows low values ​for the region and NO3-has no correlation with other ions, due to complex sources since this ion appears as a secondary aerosol.
Keywords: aerosols; antarctic; glaciochemistry; ion chromatography